Case report: Reconstruction of an intercalary defect with bone transport after resection of Ewing's sarcoma - EROL, BÜLENT (LIPPINCOTT WILLIAMS & WILKINS, 2005)
We report a 13-year-old girl with Ewing's sarcoma of the tibia who was treated with multiagent chemotherapy, followed by local control tumor surgery consisting of wide resection of the tumor and bone transport with distraction osteogenesis for reconstruction. The bone defect created by resection was 13 cm long and was replaced by bone transport using a monolateral external fixator. Evaluation of the resected specimen revealed wide tumor-free margins with 100% chemonecrosis. A planned Harmon-type autogenous bone grafting between the middle and proximal segments of the tibia (docking site) was done primarily after docking occurred, and a solid union was obtained by 23 months after resection. The bone healing index (treatment index) was 54 days/1 cm distraction, which is indicative of slow healing. Clinical evaluation of the affected extremity using the Musculoskeletal Tumor Society rating system revealed 80% normal functional capability. Indications for bone transport in reconstruction of bone defects created by wide resection of bone sarcomas are discussed. In retrospect, we have concerns regarding the suitability of this technique in the setting of diaphyseal sarcoma reconstruction in patients with Ewing's sarcoma who require aggressive and intense multiagent chemotherapy.
Keywords: DISTRACTION OSTEOGENESIS; OSTEOSARCOMA; DOXORUBICIN; ALLOGRAFTS; PROGNOSIS